(untitled) (Journal of Decolonising Disciplines, 2021)
What is unique about Ethiopia is, the history of survived colonial conquest. The Ethiopian patriotic forces defeated Italian army at the Battle of Adowa in 1896. Ethiopia has a long history of voluntarily pushing modernisation in the context of development. The major drive of modernization aimed at transforming Ethiopia from feudal ‘traditional’ society to ‘modern’ society. Hence, Ethiopia has been in-charge of its development trajectory, compared to other colonised Africans. Ironically, alike other African countries Ethiopia is still struggling with challenges of development. This is historical, an interpretive and conceptual study, executed in thematic terms. Theoretically, the study predicated on decolonial epistemic perspective, that articulates application of modernization to development, as its units of analysis. The findings indicate the need for epistimic decolonization to avoid the invasion of cognitive empire with its modernist influences of civilisation and development.